Cognitive Deficits and Associated ERP N400 Abnormalities in FXTAS With Parkinsonism - Wang, Xiao-Hong; Yang, Jin-Chen; Soohoo, Robert; Cotter, Devyn; Yuan, Mei; Xia, Jiangyi; Yaqub, Shuja; Doty, Jesse; Niu, Yu-Qiong; Tassone, Flora; Hagerman, Randi; Zhang, Lin; et al. (Frontiers in Genetics, 2018)
Abstract Objective To examine cognitive deficits and associated brain activity in fragile X-associated tremor/ataxia syndrome (FXTAS) patients with parkinsonism (FXTp+), in relation to FXTAS patients without parkinsonism (FXTp-) and normal elderly controls (NC). Methods Retrospective reviews were performed in 65 FXTAS patients who participated in the event-related brain potential (ERP) study and also had either a videotaped neurological examination or a neurological examination for extrapyramidal signs. Parkinsonism was defined as having bradykinesia with at least one of the following: rest tremor, postural instability, hypermyotonia, or rigidity. Eleven FXTp+ patients were identified and compared to 11 matched FXTp- and 11 NC. Main ERP measures included the N400 congruity effect, N400 repetition effect, and the late positive component (LPC) repetition effect. Results When compared with FXTp- and NC, the FXTp+ group showed more severe deficits in executive function, cued-recall, recognition memory, with a significantly reduced N400 repetition effect (thought to indexing semantic processing and verbal learning/memory) which was correlated with poorer verbal memory. Across all patients, FMR1 mRNA levels were inversely correlated with delayed recall on the California Verbal Learning Test (CVLT). Interpretation The findings of more prominent executive dysfunction and verbal learning/memory deficits in FXTp+ than FXTp- are consistent with findings in Parkinson’s disease (PD), and may indicate that concomitant and/or synergistic pathogenetic mechanisms associated with PD play a role in FXTAS. These results have implications not only for understanding the cognitive impairments associated with the parkinsonism subtype of FXTAS, but also for the development of new interventions for these patients.